2020
DOI: 10.1186/s12916-020-01695-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing stroke prevention therapy of direct oral anticoagulants and vitamin K antagonists in patients with atrial fibrillation: a nationwide retrospective observational study

Abstract: Background Direct oral anticoagulants (DOACs) are not only increasingly being used for the initial stroke prevention therapy but progressively also substitute vitamin K antagonist (VKA) treatment in patients with non-valvular atrial fibrillation (AF). DOACs have been compared regarding therapeutic efficacy and adverse outcomes to warfarin in several pivotal studies and showed non-inferiority in terms of stroke prevention and superiority in terms of bleeding complications. However, comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 38 publications
(69 reference statements)
8
33
1
2
Order By: Relevance
“…The SoF tables were prepared using GRADEpro GDT [40]. For estimating the absolute effect, we used absolute risks for the control group based on publications thought to be representative for routine care in western countries [15,16,18]. If we could not nd a suitable publication for one outcome, we used the risk of the comparator group of included RCTs.…”
Section: Publication Biasmentioning
confidence: 99%
See 4 more Smart Citations
“…The SoF tables were prepared using GRADEpro GDT [40]. For estimating the absolute effect, we used absolute risks for the control group based on publications thought to be representative for routine care in western countries [15,16,18]. If we could not nd a suitable publication for one outcome, we used the risk of the comparator group of included RCTs.…”
Section: Publication Biasmentioning
confidence: 99%
“…To explore this heterogeneity, we performed post-hoc subgroup analyses. We decided to stratify the analyses according to agent because previous systematic reviews and large real-world studies had suggested that dabigatran and rivaroxaban tend to have a higher bleeding risk than apixaban and edoxaban [13,15,16,18,20,54].…”
Section: Major or Clinically Relevant Bleedingmentioning
confidence: 99%
See 3 more Smart Citations